Relationship and improvement strategies between drug nanocarrier characteristics and hemocompatibility: What can we learn from the literature - Shiqi Guo; Yanan Shi; Yanzi Liang; Lanze Liu; Kaoxiang Sun; Youxin Li (Elsevier, 2021)
This article discusses the various blood interactions that may occur with various types of nano drug-loading systems. Nanoparticles enter the blood circulation as foreign objects. On the one hand, they may cause a series of inflammatory reactions and immune reactions, resulting in the rapid elimination of immune cells and the reticuloendothelial system, affecting their durability in the blood circulation. On the other hand, the premise of the drug-carrying system to play a therapeutic role depends on whether they cause coagulation and platelet activation, the absence of hemolysis and the elimination of immune cells. For different forms of nano drug-carrying systems, we can find the characteristics, elements and coping strategies of adverse blood reactions that we can find in previous researches. These adverse reactions may include destruction of blood cells, abnormal coagulation system, abnormal effects of plasma proteins, abnormal blood cell behavior, adverse immune and inflammatory reactions, and excessive vascular stimulation. In order to provide help for future research and formulation work on the blood compatibility of nano drug carriers.